In vitro study of microleakage of different techniques of surface preparation used in pits and fissures - Shahrzad Javadi Nejad; Mohamad Razavi; Reza Birang; Mohamad Atefat (Wolters Kluwer Medknow Publications, 2012)
Objective : The purpose of this in vitro study was to evaluate the effect of different techniques of surface preparation on the microleakage of a sealant applied with traditional acid etching and self-etched bonding agent. Study Design : A total of 60 extracted third molars were randomly assigned into six groups (n = 10/each). The occlusal surfaces were sealed with a sealant (Clinpro) after one of the following pretreatments: (1) phosphoric acid etching; (2) Prompt L-Pop; (3) laser + etching; (4) laser + Prompt L-Pop; (5) air abrasion + etching; (6) air abrasion + Prompt L-Pop. The specimens were immersed in a 0.5% basic fuchsin solution. Buccolingual cuts parallel to the long axis of the tooth were made. The surfaces were scored 0--2 for extent of microleakage using a microscope and the data were analyzed statistically. Results : The poorest results were obtained with laser + Prompt L-Pop which showed a greater number of specimens with microleakage (80%). Air abrasion surface preparation + phosphoric acid etching showed less microleakage than the other groups (40%). Kruskal--Wallis and t-tests revealed no significant difference in microleakage between six groups. Conclusion : The self-etching adhesive studied seems an attractive alternative to the acid-etch technique for sealant application in young children where simplifications in the clinical procedure are warranted. No significant difference was noted between the different types of enamel preparation before fissure sealant.